Finger defect coverage with digital artery perforator flaps. (December 2019) - Matei, Ileana Rodica; Bumbasirevic, Marko; Georgescu, Alexandru Valentin
Abstract: Aim: The aim of this paper is to demonstrate the advantages of using local resources in the coverage of such defects. Our approach in fingers' defects is the use of local perforator flaps, both as propeller flaps or bi-lobed pedicled flaps. Patients and methods: After performing an anatomical study on cadaver segments injected with latex followed by transparentation, 81 local perforator flaps in 80 patients during a period of 10 years (2007–2016), i.e. 47 digital artery propeller perforator flaps (DAPP), 10 island transposition perforator flaps (DATP), and 24 bi-lobed pedicled perforator flaps (BLP) were performed in our department. The patients were evaluated regarding finger mobility (ROM), two-points discrimination (TPD), and degree of satisfaction (DS) from cosmetic point of view. Results: The mean interval for social and professional reintegration was 12 days. As complications, we registered only venous congestion in 7 cases followed by epidermolysis in 4 cases and superficial necrosis in 3 cases, which healed by reepithelialization. The range of motion (ROM) of the reconstructed fingers was normal in all the patients. All the flaps regain a satisfactory degree of sensibility (TPD between 4 mm and 14 mm). The DS was relatively high, with 67 patients very satisfied, 11 satisfied, and 2 unsatisfied. Conclusions: This fast and less invasive method, which replaces like-with-like, allows an early and good reinervation and a rapid social and professional reintegration, proves to be a very reliable alternative in digital defects coverage.